2023
DOI: 10.1021/jacs.3c04732
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Design for Catalytic Dehydration: Direct, Room-Temperature Esterification without Acid or Base Additives

Jian Han,
Christopher A. Haines,
Jacob J. Piane
et al.

Abstract: An electrochemical approach has been leveraged to underpin a new conceptual platform for dehydration reactions, which has been demonstrated in the context of esterification. Esters were prepared from the corresponding acid and alcohol partners at room temperature without acid or base additives and without consuming stoichiometric reagents. This methodology therefore addresses key complications that plague esterification and dehydration reactions more broadly and that represent a leading challenge in synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…( 1). This chemoselectivity was also reported by Nacsa, [29] and others [30] in photochemical system, which indicates the phosphorus radical cation may preferentially activate acid [22a] in the presence of alcohol.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…( 1). This chemoselectivity was also reported by Nacsa, [29] and others [30] in photochemical system, which indicates the phosphorus radical cation may preferentially activate acid [22a] in the presence of alcohol.…”
Section: Methodssupporting
confidence: 81%
“…These structures were determined through a combination of chemical shift and literature precedents [26] (see Supporting Information for details). Similarly, a wide range of mono-, di-, and polysubstituted phenols also gave the corresponding aryl alkyl ether (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) in high yields and ee's. For the monocyclic five-membered heterocycles (32-49), N-alkylation in general readily takes place to give products in high yield, except for pyrroles (43-45), which are prone to decompose under oxidative conditions.…”
Section: Methodsmentioning
confidence: 93%
“…Indirect electrolysis using organic mediators are efficient for the construction of C−O bond [80–88] . In 2016, Baran et al.…”
Section: Electrochemical Reactions Using Organic Mediatorsmentioning
confidence: 99%
“…Indirect electrolysis using organic mediators are efficient for the construction of CÀ O bond. [80][81][82][83][84][85][86][87][88] In 2016, Baran et al reported an electrochemical allylic CÀ H oxidation using tetrachloro-Nhydroxyphthalimide (Cl 4 NHPI) as the mediator. [80] In 2017, they reported the more versatile electrochemical oxidation of unactivated CÀ H bonds using quinuclidine as an organic mediator (Scheme 33).…”
Section: Cà O Bond Formation Using Organic Mediatormentioning
confidence: 99%
“…In the report by Wasserman et al, it is mentioned that, apart from singlet oxygen, the participation of reducing agents such as diphenyl sulphide is also important in the production of imidazoline derivatives. 10,14,15 Therefore, we suspect that phenothiazine can act as a reducing agent due to the presence of heteroatom S. The participation of phenothiazine can efficiently produce DYZ derivatives without the addition of any photosensitisers and reducing agents.…”
mentioning
confidence: 99%